SME financing for small and middle entrepreneurs in Bangladesh: reviewing from the perspective of BRAC Bank Ltd. - Halder, Nilanjana (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.